Quality of prison life, violence and mental health in Dubrava prison. Issue 3 (31st May 2019) - Skar, Mette; Lokdam, Nicoline; Liebling, Alison; Muriqi, Alban; Haliti, Ditor; Rushiti, Feride; Modvig, Jens
Abstract : Purpose: The purpose of this paper is to explore the association between the quality of prison life and mental health among prisoners and the occurrence of violence. Design/methodology/approach: In total, 203 prisoners from Dubrava Correctional Center in Kosovo participated. Data on background characteristics of the prisoners, quality of prison life, mental health symptoms and exposure to physical, psychological and sexual violence were collected through interviewer-administered questionnaires. Data were analyzed using general linear models (GLM) and manual backwards model search with step-wise exclusion. Findings: The GLM analysis showed a significant negative association between anxiety symptom load (−1.4), physical violence (−1.5) and psychological violence (−1.9), and quality of prison life. Furthermore, it appeared that prisoners rating of quality of life (QoL) increased with time among prisoners not exposed to violence, while this was not seen among prisoners exposed to violence. Finally, there was an inverse association between the dimensions of respect, fairness, humanity and good staff/prisoner relations, and the proportion of prisoners exposed to violence. Originality/value: An environment with higher levels of respect, fairness, humanity and good relations between staff and prisoners was associated with lower levels of violence. Hence, a prison that focuses on promoting QoL and good mental health among prisoners will show lower levels of violence, thereby making the prison a more tolerable place for the prisoners and a better working environment for prison staff.